AI superstream : NLP in production (O'Reilly Media, Inc., 2022)
Natural language processing is one of the most widely used branches of machine learning, with applications ranging from the widespread and high impact to the cutting edge. Join practitioners from various industries as they highlight the challenges and possibilities of working with NLP.